Cognitive Behavioral Therapy Management of a Patient with Atypical Anorexia Nervosa - Liyanage, Nisansala; Suraweera, Chathurie; Rodrigo, Asiri (Case Reports in Psychiatry, 2019)
Eating disorders are becoming more common in nonwestern societies and some of these presentations are atypical variants such as atypical anorexia nervosa. There is very little data on how to treat these patients. This case study reports the treatment of a young adult female in Sri Lanka who presented with atypical anorexia nervosa and moderate depressive disorder. She was successfully treated with nine sessions of enhanced cognitive-behavioural therapy (CBT-E). According to our knowledge this is the first case report that describes the management of a patient with atypical anorexia nervosa using psychological therapy specifically adapted to nonwestern context.